Chinese herbal foot baths as a new strategy for diabetic foot with Wagner grade of 0 or 1: a meta-analysis and data mining - Ruifang Lin; Yunfeng Yu; Yuman Yin; Xiu Liu; Yongjun Wu; Qin Xiang; Yaoyue Luo; Rong Yu (Frontiers in Pharmacology, 2025)
ObjectiveThe benefit of Chinese herbal foot-baths in treating diabetic foot remains unclear. This study aims to assess the efficacy of Chinese herbal foot-baths for diabetic foot with Wagner grade of 0 or 1 and identify key candidate herbs.MethodsA comprehensive search of eight databases was conducted for studies published up to 24 May 2025. Relevant data on study characteristics, outcomes, and risk of bias were extracted. The meta-analysis and trial sequential analysis (TSA) were performed using RevMan 5.3 and TSA 0.9.5.10 beta, respectively. The risk ratio (RR) and mean difference (MD) were respectively used as effect sizes for dichotomous and continuous outcomes. Publication bias was assessed with funnel plots and Egger’s tests.Results13 studies involving 921 participants were included in this review. The meta-analysis showed that compared to warm water foot-bath, Chinese herbal foot-baths significantly improved the clinical effective rate (RR 1.42, 95%CI 1.31–1.53, p < 0.00001), ankle-brachial index (MD 0.19, 95%CI 0.11–0.26, p < 0.00001), common peroneal nerve motor nerve conduction velocity (MD 4.09, 95%CI 2.41–5.77, p < 0.00001), common peroneal nerve sensory nerve conduction velocity (MD 3.83, 95%CI 2.48–5.17, p < 0.00001). The glycosylated hemoglobin A1c (MD -0.15, 95%CI -0.30–0.01, p = 0.04), and fasting blood glucose levels (MD -0.28, 95%CI -0.54–0.02, p = 0.04) were significantly reduced. However, no significant differences were observed in 2-h postprandial blood glucose, total cholesterol, triglycerides, and adverse events (p > 0.05). Additionally, except for the clinical effective rate, there are no potential publication biases in other results. Furthermore, the data mining identified the key candidate herbs used in the foot bath as [Cinnamomum cassia Presl], [Conioselinum anthriscoides ‘Chuanxiong'], [Paeonia lactiflora Pall.], [Angelica sinensis (Oliv.) Diels] [Prunus persica (L.), Batsch], [Carthamus tinctorius L.], and [Asarum heterotropoides F. Schmidt].ConclusionChinese herbal foot-baths can improve clinical symptoms as well as vascular and nerve functions in diabetic foot patients with Wagner grades 0 or 1, without increasing the incidence of adverse events. The seven herbs identified through data mining offer a reference for formulating Chinese herbal foot-baths. However, these clinical findings and the pharmacological effects of the herbal combinations require further validation.Systematic Review Registrationwww.crd.york.ac.uk/PROSPERO/view/CRD42024615181, CRD42024615181